Oleuropein induces apoptosis via abrogating NF‐κB activation cascade in estrogen receptor–negative breast cancer cells. Issue 3 (27th September 2018) - Liu, Lian; Ahn, Kwang Seok; Shanmugam, Muthu K; Wang, Hong; Shen, Hongyuan; Arfuso, Frank; Chinnathambi, Arunachalam; Alharbi, Sulaiman Ali; Chang, Yung; Sethi, Gautam; Tang, Feng Ru
Abstract: Oleuropein is one of the most abundant phenolic compounds found in olives. Epidemiological studies have indicated that an increasing intake of olive oil can significantly reduce the risk of breast cancer. However, the potential effect(s) of oleuropein on estrogen receptor (ER)‐negative breast cancer is not fully understood. This study aims to understand the anticancer effects and underlying mechanism(s) of oleuropein on ER‐negative breast cancer cells in vitro. The effect of oleuropein on the viability of breast cancer cell lines was examined by mitochondrial dye‐uptake assay, apoptosis by flow cytometric analysis, nuclear factor‐κB (NF‐κB) activation by DNA binding/reporter assays and protein expression by Western blot analysis. In the present report, thiazolyl blue tetrazolium bromide assay results indicated that oleuropein inhibited the viability of breast cancer cells, and its effects were more pronounced on MDA‐MB‐231 as compared with MCF‐7 cells. It was further found that oleuropein increased the level of reactive oxygen species and also significantly inhibited cellular migration and invasion. In addition, the activation of NF‐κB was abrogated as demonstrated by Western blot analysis, NF‐κB‐DNA binding, and luciferase assays. Overall, the data indicates that oleuropein can induce substantial apoptosis via modulating NF‐κB activation cascade in breast cancer cells. Abstract : Oleuropein mitigates migration and invasion via abrogating NF‐κB activation cascade in ER‐negative breast cancer cells.